Bank Capital Structure Dynamics and Covid-19: Evidence from South Asia - Mohammad, Khalil Ullah; Khan, Mohsin Raza (iRASD Journal of Economics, 2021)
The severity in terms of economic activity of the Covid-19 crisis was higher than the global financial crisis. Covid-19 has not only challenged the economic activity across the world but has put to test how the bank operates under the global crises. The objective of this paper is to identify the impact of the Covid-19 crisis on the South Asian banking sector. We investigate if South Asian banks have target leverage and how the Covid-19 crisis impacted their capital structure dynamics. To fulfill the objective, past data on all banks of South Asian countries listed in the Thomson Reuter Refinitiv were considered. The sample ended up including quarterly data of banks from India, Pakistan, Bangladesh, Sri Lanka, Bhutan Nepal and Afghanistan. Engle-Granger's two-step procedure for error correction and two-step GMM estimation was employed to measure the speed of adjustment and the impact of Covid-19 on bank capital. The study found that the capital structure determinants favor the static trade-off theory for South Asian banks. It is also observed that South Asian banks’ capital was negatively impacted by Covid-19. The analysis supports the view of leverage convergence for the capital structure. This study improves our understanding of the capital structure dynamics of banks in response to exogenous shocks in South Asia.